EVALUASI SKALA PRIORITAS KINERJA JARINGAN DRAINASE - Sumarno, Wahyu; Defiana , Yanti; Pratiwi , Fina (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
Tasikmalaya City is one of the cities located in the southeastern part of West Java Province, included in 2 (two) watersheds, namely Citanduy and Ciwulan. The condition of the existing canal in the City of Tasikmalaya is still considered insufficient to accommodate the overflow of rainwater, so that many areas are still inundated. This study looks for the priority scale of thinking handling, knowing the performance of drainage in the selected location, and getting the concept of handling the drainage channel at the selected location. Channel channel priority scale using ANP software. Performance is reviewed based on discharge at 1, 2, and 5 years by using SWMM. The concept of improving the drainage system is carried out using two scenarios, namely increasing the dimensions of the channel and reducing the amount of air runoff by making infiltration wells. The results of the analysis show that the priority of channel repairs on Jl. HZ Mustofa. The channel capacity is based on the discharge of the 1 year return period there are 11 overflowing drainage channels, the 2 year return period there are 15 overflowing drainage channels and the 5 year return period there are 16 overflowing drainage channels from 43 drainage channels. The concept of canal management can be implemented, but there are land constraints. If the infiltration well is applied in accordance with the calculation results, the 1-year return discharge is reduced by 24.65%, the 2-year return period is reduced by 19.63%, and the 5-year return period is 18.18%. However, the use of infiltration wells is considered ineffective to reduce rainwater runoff, but has a positive impact on groundwater conservation.